DESIGN OF A CLOTHING SALES INFORMATION SYSTEM BASED ON JAVA NETBEANS USING THE WATERFALL METHOD - Achmad Yudha Pratama; Ika Ratna Indra Astutik (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to develop an efficient and integrated information system to optimize the management of clothing sales within Micro, Small, and Medium Enterprises (MSMEs) in the retail sector, particularly those still operating with manual processes that are time-consuming and prone to errors. Method: The research employs the Waterfall model as a systematic software development approach, encompassing stages of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using Java programming language with NetBeans IDE as the development environment and MySQL as the database management system. Results: The resulting Java-based Clothing Sales Information System successfully automates key business processes, including inventory management, transaction recording, and sales reporting, thereby improving data accuracy and operational efficiency. Novelty: The study contributes by presenting a practical and scalable information system model tailored to the needs of MSMEs in the retail clothing industry, demonstrating how digital transformation can enhance competitiveness and streamline business management in the era of globalization.